Long-term potentiation of C-fiber-evoked potentials in the rat spinal dorsal horn is prevented by spinal N-methyl-d-aspartic acid receptor blockage - Liu, Xianguo; Sandkühler, Jürgen (Neuroscience letters, 1995)
Long-term potentiation (LTP) of synaptic potentials is a fundamental mechanism of memory formation in the hippocampus. Here, we have characterized long-term changes of field potentials which were evoked in the lumbar spinal dorsal horn by supramaximal electrical stimulation of the sciatic nerve in urethane anesthetized rats. The field potentials had high thresholds (≥7 V), long latencies 90-130 ms, corresponding to conduction velocities between 1.2 and 0.85 m/s) and were not affected by spinalization (at C5-C6) or muscle relaxation (with pancuronium), i.e. the potentials were probably evoked by afferent C-fibers. Tetanic electrical stimulation (0.5 ms pulses, 30-40 V, 100 Hz, given in 4 trains of 1 s duration at 10 s intervals) of sciatic nerve induced in all 9 rats tested a LTP of amplitude of the C-fiber-evoked potential throughout recording periods which lasted between 4 and 9 h. Mean potentiation ranged from +71% to +174%. Superfusion of spinal cord with N-methyl-d-aspartic acid (NMDA) receptor antagonist d-(−)-4-(3-phosphonopropyl)piperzine-2-carboxylic (500 nm), which has little effect on the amplitude of C-fiber-evoked potentials, completely blocked LTP induced by tetanic stimulation in all five rats tested. Superfusion of spinal cord with NMDA (1 μM, 10 μM or 50 μM) induced LTP in only 2 out of 8 rats. This is the first report showing that LTP of C-fiber-evoked field potentials in the spinal dorsal horn in vivo may last for more than 8 h. This LTP in the spinal dorsal horn may underlie plastic changes of spinal nociception.
Online 14 January 2000
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 03.05.2021